Simultaneous pulmonary and intrathoracic lymph nodal granulomatosis of unknown significance (GLUS) - S. Katsenos; K. Kostikas; S. Lachanis; D. Sabaziotis; K. Psathakis; S. Loukides (Monaldi Archives for Chest Disease, 2004)
A case of a 30-year-old male with a fever, dry cough and associated abnormal findings in imaging modalities (bilateral hilar lymphadenopathy and nodular parenchymal opacities) is described. After a further and scrutinized work-up, the diagnosis of GLUS syndrome was made. Clinical, etiological, pathological and therapeutical aspects of the disease are discussed, demonstrating the paramount importance of the use of the immunohistochemical methods in the diagnosis of this disorder.